Identifying and characterizing cancer survivors in the US primary care safety net. Issue 19 (7th June 2019) - Hoopes, Megan; Schmidt, Teresa; Huguet, Nathalie; Winters‐Stone, Kerri; Angier, Heather; Marino, Miguel; Shannon, Jackilen; DeVoe, Jennifer
Abstract : Background: Primary care providers must understand the use patterns, clinical complexity, and primary care needs of cancer survivors to provide quality health care services. However, to the authors' knowledge, little is known regarding the prevalence and health care needs of this growing population, particularly in safety net settings. Methods: The authors identified adults with a history of cancer documented in primary care electronic health records within a network of community health centers (CHCs) in 19 states. The authors estimated cancer history prevalence among >1.2 million patients and compared sex‐specific site distributions with national estimates. Each survivor was matched to 3 patients without cancer from the same set of clinics. The demographic characteristics, primary care use, and comorbidity burden then were compared between the 2 groups, assessing differences with absolute standardized mean differences (ASMDs). ASMD values >0.1 denote meaningful differences between groups. Generalized estimating equations yielded adjusted odds ratios (aORs) for select indicators. Results: A total of 40, 266 cancer survivors were identified (prevalence of 3.0% of adult CHC patients). Compared with matched cancer‐free patients, a higher percentage of survivors had ≥6 primary care visits across 3 years (62% vs 48%) and were insured (83% vs 74%) (ASMD, >0.1 for both). Cancer survivors had excess medical complexity, including a higher prevalence of depression, asthma/chronic obstructive pulmonary disease, and liver disease (ASMD, >0.1 for all). Survivors had higher odds of any opioid prescription (aOR, 1.23; 95% CI, 1.19‐1.27) and chronic opioid therapy (aOR, 1.27; 95% CI, 1.23‐1.32) compared with matched controls ( P  < .001 for all). Conclusions: Identifying cancer survivors and understanding their patterns of utilization and physical and mental comorbidities present an opportunity to tailor primary health care services to this population. Abstract : The current large, observational study using primary care electronic health record data demonstrates several important findings regarding adult cancer survivors, including substantial differences in primary care use and health insurance patterns, excess comorbidity, and disparities in chronic pain and opioid use compared with matched cancer‐free counterparts. As more patients continue to survive cancer, the role of primary care providers in providing long‐term, comprehensive follow‐up care is increasing.